Efficiency of seed treatment with fungicides in castor bean crop genotypes - Poletine, Juliana Parisotto; de Goes Maciel, Cleber Daniel; da Silva, Tiago Roque Benetoli; Zanotto, Maurício Dutra [UNESP] (My University, 2012)
With the objective of assessing castor bean genotypes in relation to the influence of seeds treatment on agronomic characteristics and physiological quality of seeds, two experiments were conducted between November, 2005 and March, 2006. In the first study, experimental design used was randomized complete blocks, in factorial scheme (2×10), by comparing Lyra hybrid and AL Guarany 2002 cultivar and nine fungicides, including its mixtures and test, with four repetitions. Plant height, stem diameter, medium yield and observation of diseases incidence were evaluated. In the second study, conducted in randomized entirely design, in factorial scheme 2×10 with four repetitions, Savana and AL Guarany 2002 genotypes were analyzed, using the same fungicides. Germination, infected and dead seeds, vigor, initial moisture content and simulation of field emergency and seeds sanitary quality were also evaluated. The results obtained point that there is positive influence of seed treatment on agronomic characteristics in castor bean crop, increasing grain yield for AL Guarany cultivar and Lyra hybrid. In the analysis of seed quality, it was observed that seed treatments with fungicides and their mixtures provided superior percentages of germination and vigor, reduced the number of infected and dead seeds and increased seeds emergency for AL Guarany 2002 cultivar and Savana hybrid.
Keywords: Genotype; Phytosanitary; Ricinus communis L.; Yield